The effects of native lactic acid bacteria on the microbiome, fermentation profile, and nutritive value of Napier grass silage prepared with different legume ratios - Guan, Hao; Li, Haiping; Gan, Li; Chen, Shiyong; Yan, Yanhong; Jia, Zhifeng; Liu, Wenhui; Wei, Xiaoxing; Ma, Xiang; Zhou, Qingping (Frontiers in Microbiology, 2023)
Abstract: Mixing grass with legumes before ensiling is beneficial for improving dry matter and crude protein yield, but additional information is needed to balance nutrient content and fermentation quality. In this study, the microbial community, fermentation characteristics, and nutrient content of Napier grass mixed with alfalfa at different proportions were assessed. Tested proportions included: 100:0 (M0), 70:30 (M3), 50:50 (M5), 30:70 (M7), and 0:100 (MF). Treatments included: (CK) sterilized deionized water; (IN) selected lactic acid bacteria: Lactobacillus plantarum CGMCC 23166 and L. rhamnosus CGMCC 18233 (1.5 × 105 cfu/g of fresh weight for each inoculant); (CO) commercial lactic acid bacteria: L. plantarum (1 × 105 cfu/g of fresh weight). All mixtures were ensiled for 60 d. Data analysis used as a completely randomized design with a 5-by-3 factorial arrangement of treatments. The results showed that with increasing alfalfa mixing ratio, dry matter and crude protein increased, while neutral detergent fiber and acid detergent fiber decreased both before and after ensiling (P < 0.05), which was not influenced by fermentation. Inoculation with IN and CO decreased pH and increased the lactic acid content compared to CK (P < 0.05), especially in silages M7 and MF. The highest Shannon index (6.24) and Simpson index (0.93) were observed in the MF silage CK treatment (P < 0.05). The relative abundance of Lactiplantibacillus decreased with increasing alfalfa mixing ratio, while the abundance of Lactiplantibacillus was significantly higher in the IN-treated group than in other treatment groups (P < 0.05). A higher alfalfa mixing ratio improved the nutrient value, but also made fermentation more difficult. Inoculants improved the fermentation quality by increasing the abundance of Lactiplantibacillus. In conclusion, the groups M3 and M5 achieved the optimal balance of nutrients and fermentation. If a higher proportion of alfalfa needs to be used, it is recommended to use inoculants to ensure sufficient fermentation.